Effect of Transformations of Russian Society on Forming of Value Orientation of Today Youth (on an Example of Sverdlovskaya Region) - GLUKHOV, Vladimir Vladimirovich; PONOMAREVA, Olga Yakovlevna (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
Scientific and technical progress, evolution of relations between the state as substituting whole and its elements – population, form the base of emergence and revealing new types of contradictions in different spheres of society functioning. Relatively wide range of terms that describe the category of population under research as well as used concepts are used depending on the branch of knowledge, scientific school and author point of view of researcher. New approaches to study of the problem of younger generation are required relevant to globalization and internationalization of economic relations. These approaches should fix the necessity of generalization of requests and possibilities of capable of working population aged 14-30, reveal general theoretical and practical basics of young people behaviour. This trend may indicate both irrelevance of the content and technologies of getting of higher professional education to changed labor market and change of relation of the Generation Y to the value of labor as a way of self-fulfillment and reveal of potential.
Keywords: youth, transformation of generations, education, labor market, qualities of personality, value orientation